Aplikasi Arduino Uno R3 pada Exhaust System Engine SAA12v140e-3 HD 785-7 untuk Meningkatkan Nilai Intelligence - Umbaran, Retno; Farid, Akhmad; Finahari, Nurida (Widyagama University of Malang, 2024)
The condition of the HD785-7 unit which is more than 30,000 hourmeters old and the working environment is difficult, and there has never been any checking and maintenance on the exhaust gas temperature, this causes the exhaust gas temperature sensor and electrical system to be neglected which results in inaccurate reading of the exhaust gas temperature value in the VHMS (Vehicle Health Monitoring System) which makes the achievement of IA (Intelligence Availability) worsen for the HD785-7 unit at PT Pamapersada Nusantara on the KPCS site. After making observations through the data, an implementation of the exhaust gas temperature value improvement program was carried out by placing the exhaust gas temperature sensor properly, routable the VHMS (Vehicle Health Monitoring System) wiring harness, and repairing the exhaust gas temperature system wiring with the target of reducing the number of error and abnormal readings on the exhaust gas temperature value in the VHMS (Vehicle Health Monitoring System), so that the achievement of IA (Intelligence Availability) is in accordance with the target of the KPCS site of PT Pamapersada Nusantara, which is 75%. After the exhaust gas temperature value improvement program was carried out and monitoring of the IA (Intelligence Availability) data was carried out, the error reading and abnormal values ​​​​of the exhaust gas temperature decreased to 56.75%, the result was that the IA (Intelligence Availability) achievement increased to 83.85% and reached the IA (Intelligence Availability) achievement target from PT Pamapersada Nusantara, which was 75%.